Urgensi Wacana Bahasa Indonesia Lebih Pantas sebagai Bahasa Kedua ASEAN daripada Bahasa Melayu dalam Perspektif Identitas Nasional Indonesia - Brillian Najwa Nayantaka; Suryo Ediyono (Jurnal Global Citizen : Jurnal Ilmiah Kajian Pendidikan Kewarganegaraan, 2026)
The emergence of the discourse on the use pg Indonesian as the second language of ASEAN as Indonesia's response to the proposal of Malah as the second language of ASEAN by Malaysia has triggered a threat to the position of Indonesian as the national identity of the Indonesian Nation, as well as providing opportunities and motivating factors for Indonesian in launching its vision to become an international language. This article was compiled using the literature study method, namely with a qualitative approach by examining sources related to the Indonesian language as a national identity which was then used as a point of fire in studying this discourse. So thatit can be seen how the condition of appropiateness for one of two languages to be used as the second language of ASEAN, where Indonesian language dominates in its role as national identity.